2020
DOI: 10.1016/j.trecan.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Mechanisms by which EMT Programs Control Stemness

Abstract: Tissue regeneration relies on adult stem cells (SCs) that possess the ability to self-renew and produce differentiating progeny. In an analogous manner, the development of certain cancers depends on a subset of tumor cells, called cancer stem cells (CSCs), with SC-like properties. In addition to being responsible for tumorigenesis, CSCs exhibit elevated resistance to therapy and thus drive tumor relapse post-treatment. The epithelial-mesenchymal transition (EMT) programs promote SC and CSC stemness in many epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 40 publications
3
133
0
1
Order By: Relevance
“…As there are several molecular pathways exploited by breast cancer cells with EMT, along with those residing in a stem-like state [ 22 ], these mechanisms were also confirmed in our study. In particular, it was observed that CSCs are closely related to EMT, and that EMT is likely to be critical in tumor invasion and metastasis [ 17 , 23 ]. Furthermore, CSCs are responsible for tumorigenesis-associated processes, as these cells display increased resistance to therapy, even promoting tumors post-treatment relapse [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As there are several molecular pathways exploited by breast cancer cells with EMT, along with those residing in a stem-like state [ 22 ], these mechanisms were also confirmed in our study. In particular, it was observed that CSCs are closely related to EMT, and that EMT is likely to be critical in tumor invasion and metastasis [ 17 , 23 ]. Furthermore, CSCs are responsible for tumorigenesis-associated processes, as these cells display increased resistance to therapy, even promoting tumors post-treatment relapse [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was observed that CSCs are closely related to EMT, and that EMT is likely to be critical in tumor invasion and metastasis [ 17 , 23 ]. Furthermore, CSCs are responsible for tumorigenesis-associated processes, as these cells display increased resistance to therapy, even promoting tumors post-treatment relapse [ 17 ]. Thus, identification of transcriptional markers for these two pathways in order to understand resistance towards some of the most prevalently used therapies for treatment of breast cancer will greatly benefit breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial in vitro and in vivo studies have provided convincing evidence supporting CSCs as the critical cause of cancer initiation, growth, metastasis, and treatment resistance in cancers [20][21][22][23][24] . CSCs were also found to exhibit characteristics of an EMT, a process known to enable cancer cell dissemination and metastasis to other organs [35][36][37][38][39][40][41] . Additionally, significant and convincing evidence shows that inducing EMT in cancer cells confers cancer stem cell-like characteristics, which promote their metastatic and tumor-initiating abilities [37,38] .…”
Section: Pcscsmentioning
confidence: 99%
“…As spheroid culture has been shown to enrich for cells with stem cell properties, these findings suggest that intrinsic stemness-independent of exogenous treatments-may be associated with a more mesenchymal phenotype. The relationship between the EMT and stemness is well documented 12,32 , but there is growing evidence that stemness and EMT are not inextricably linked. For example, the EMT-promoted transcription factor PRRX1 suppresses stemness in breast cancer cells 33 .…”
Section: Brca1 Loss Promotes Emt-independent Stemness In Mosementioning
confidence: 99%